Discovery of an Unexpected Metal Dissolution of Thin‐Coated Cathode Particles and Its Theoretical Explanation. Issue 5 (10th March 2020) - He, Yufang; Pham, Hiep; Gao, Yan; Patel, Rajankumar L.; Sarkar, Susmita; Liang, Xinhua; Park, Jonghyun
Abstract: The degree of metal dissolution of cathode materials is a critical parameter in determining the performance of lithium‐ion batteries (LIBs). Ultra‐thin coated cathode particles, fabricated via atomic layer deposition (ALD), exhibit superior battery performance over that of bare particles. Therefore, it is generally believed that a coating layer protects the particles from metal dissolution of active materials, which is a critical cathode degradation mechanism. However, it is observed that ultra‐thin CeO2 coating intensified the Mn dissolution of LiMn2 O4 (LMO) during cycling of LIBs, whereas ultra‐thin Al2 O3 coating tended to inhibit Mn dissolution. A detailed density functional theory (DFT) study is carried out to explain these experimental observations by analyzing interaction of Mn atoms with neighboring electrode atoms in terms of energetic and structural aspect. All atomic and electronic analyses are consistent with the experimental observations. Several common materials are investigated as possible ALD coatings for LIBs to provide general insight, and it is found that Mn dissolution can be suppressed or accelerated depending on the material selection. This is the first report finding that depending on the coating material, metal dissolution can be accelerated, providing new insights into the impact of ALD coating materials on metal dissolution in cathode materials. Abstract : It is found that Mn dissolution can be suppressed or accelerated depending on coating material; an Al2 O3 coating prevents dissolution while a CeO2 coating intensifies it. To confirm this experimental observation, a detailed study with first‐principles calculation is conducted and is consistent with the experimental findings.